INDONESIAN CIVIL SERVICE MANAGEMENT AND CORRUPTION - Syarif Ali (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
Indonesian government has tried to reform every aspect of the country including civil service system. A legal background was established by the Law No. 5/2014. The aim of this law is to improve the competitiveness of the Indonesian bureaucracy, therefore personnel management – is critical. Effective Civil service management is considered as a key element to create good civil servant since the human element is involved in realizing good governance. This study seek to answer the research problem, – what areas are prone to open the door of corruption, collusion and nepotism. For this purpose literature is conducted to analyze data from various sources. The research finding showed that some areas such as recruitment, placement, promotion and training are positively related to corruption, collusion and nepotism.